The Influence of Indoor Comfort in Bandung Creative Hub on Supporting Users' Creative Activities - Firdaus , Adam; Zakaria, Ardika Muhamad; Putri, Tika Novis (Department of Architecture, Faculty of Engineering, University of Muhammadiyah Aceh, 2025)
Bandung is one of the cities experiencing rapid development in the creative industry, supported by various facilities, one of which is the Bandung Creative Hub (BCH). The Bandung Creative Hub serves as a platform for the community to create, innovate, and collaborate in various creative fields. However, the success of a creative hub in supporting the effectiveness of its facilities does not solely depend on the availability of space and amenities but also on the level of indoor comfort, which can influence the productivity and creativity of its users. Optimal indoor comfort creates a more conducive atmosphere for users to express their ideas and creative concepts. Therefore, this study aims to analyze the influence of indoor comfort on creative activities at the Bandung Creative Hub by examining aspects such as thermal comfort, lighting comfort, acoustic comfort, ergonomics, as well as aesthetics and spatial atmosphere. The research methods used include a questionnaire survey of visitors to the Bandung Creative Hub and direct observation to identify the conditions of spatial comfort. The results indicate that, overall, the indoor comfort of the Bandung Creative Hub is considered quite good, but several aspects still need improvement in terms of facilities and space management. One of the main concerns is the relatively high noise levels in certain areas, which may disrupt users' concentration when engaging in creative activities. Additionally, the spatial layout is not yet fully optimized to facilitate interaction and collaboration among users effectively. Based on this study, several improvements need to be made to the Bandung Creative Hub, particularly in enhancing facility quality, managing noise levels, and optimizing spatial arrangements to be more flexible and aligned with user needs. With these improvements, BCH is expected to create a more comfortable and conducive environment that supports productivity and fosters innovation in Bandung's creative industry.